2021
DOI: 10.3390/su13095044
|View full text |Cite
|
Sign up to set email alerts
|

Family Control and Corporate Innovation in Stakeholder-Oriented Corporate Governance

Abstract: This study investigates the effects of family control on corporate innovation activity in publicly traded firms in Japan under stakeholder-oriented corporate governance. In a sample of 14,991 firm-year observations in publicly traded firms in Japan during the period 2007 to 2016, we tested whether family owners or board members are enhancing research and development investments. While theoretical perspectives of principal–principal conflicts generally assume a negative relationship between family control and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
1
8
0
1
Order By: Relevance
“…The study also found a significant relationship between employee orientation and supply chain orientation, which supports the findings of reference [ 11 , 27 ]. Shareholder orientation also showed a significant effect on supply chain orientation, which aligns with the findings of reference [ 5 , 6 , 58 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The study also found a significant relationship between employee orientation and supply chain orientation, which supports the findings of reference [ 11 , 27 ]. Shareholder orientation also showed a significant effect on supply chain orientation, which aligns with the findings of reference [ 5 , 6 , 58 ].…”
Section: Discussionsupporting
confidence: 90%
“…Hence, a strong stakeholder orientation reduces the trade-offs that a limited pursuit of shareholder orientation imposes on firm innovativeness [ 6 ]. Moreover, shareholder orientation improves organisational performance because shareholders support the firm's activities when those actions align with their expectations [ 57 , 58 ].…”
Section: Theoretical Lens and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholder-oriented corporate governance, however, has the potential to address PP conflicts through monitoring by a network of stakeholders, including shareholders, creditors, employees, and government (Young et al, 2008). In particular, because Japanese companies develop strong inter-company networks in terms of financial, personal, and business relationships, managers of Japanese companies seek to achieve goals that are beneficial to all stakeholders, including non-controlling shareholders (Desender et al, 2016;Lincoln & Gerlach, 2004;Sakawa & Watanabel, 2021;Yoshimori, 1995). In fact, Sakawa and Watanabel (2018) focused on the listed subsidiaries in Japan, revealing that the sales growth rate is greater in listed subsidiaries with strong parent company control; this finding suggested that PP conflicts are less likely to surface in Japan.…”
Section: Pp Conflicts and Stakeholder-oriented Corporate Governancementioning
confidence: 99%
“…Among developed countries, Japanese corporate governance is stakeholder-oriented [8,9]. In fact, corporate innovations progress in family firms with stakeholder orientation [10]. Sustainable corporate performance and growth are also realized in effective monitoring mechanisms under stakeholder-oriented corporate governance in Japan [11].…”
Section: Introductionmentioning
confidence: 99%